Good Bacteria and Worms: As Promising Candidates for Inflammatory Bowel Disease - Hossein Ghalehnoei; Javad Akhtari; Hamed Kalani; Mahdi Fakhar (Journal of Mazandaran University of Medical Sciences, 2018)
The gastrointestinal system harbors various microorganisms, known as gut microbiota. Increase in prevalence of inflammatory bowel disease (IBD) in developed countries is associated with changes in the environment, such as decrease in incidence of parasitic infections, especially helminths, and changes in the intestinal flora. Probiotics are useful microbiota for human health. The parasitic worms (helminths) have evolved over the years with their host. Several studies have investigated the capability of helminths and probiotics to alter or control host immune responses in view of the fact that these organisms have immunomodulation effects. Given the contradictory results, further broad studies are needed to confirm the role of probiotics and helminths in the treatment of IBD.